UPAYA PENINGKATAN PSYCHOLOGICAL WELL-BEING NARAPIDANA NARKOBA MELALUI PELATIHAN MENTAL DI RUTAN KELAS II B - Tresella Frisca Seftilia; Janottama Yudianto; Endang Lestari; M. Hamdan Al Makki; Onny Anggara (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
Drug offenders are the largest contributing numbers in Indonesia’s list of prisoners. The misuse of narcotics which transpires across many demographic causes the problem to be difficult to solved. As of the case with former prisoner/ex-convict which often comes in and out of conviction with the same case (recidivist). This recidivist behavior is caused by the low amount of psychological well-being which then causes the decline of mental health. With that in mind, we intend to increase the psychological well-being of these drug offenders by giving a treatment in the form of  mental training (psychological well-being training) to the prisoners currently held in said jail. Aside from increasing the psychological well-being, this training aims to help reduce the tendency of recidivist in the future. The methods of collecting data that are used includes interviews, observations, and questionnaires. Meanwhile the method of practice that are used includes lectures, discussions and assignments. The implementation of this program gave a positive result on the psychological well-being and  mental health of the drug offenders of Class II B Jail of Bangkalan especially in facing the daily life soon after being released from jail.